Profesoriaus Igno Jonyno vaidmuo komplektuojant ir superkant istorinę literatūrą Lietuvos (vėliau Vytauto Didžiojo) universiteto bibliotekai 1926–1933 m. - Labanauskienė, Danutė (Knygotyra, 1995)
The Lithuanian University (later Vytautas Magnus University) was established in 1922 02 16 and it’s library was opened in 1923 01 01. The initial book stock was inherited from the Higher Courses. The fund was’nt plentiful and it did’nt satisfy the requirements of the university. The means, assigned from State budget for requisition of books, were received from the society as a gift. Later the means for books increased, but not much and they were subsided from the budget about 52,2 thousands litai every year. The marketable books made up hardly 27% of all the quantity. A matter of great importance was to know which of them are indispensable for the university. Professors of the university as specialists on their scientific sphere were capable to choose the best scientific works. One of them prof. Ignas Jonynas (1884–1954) well-known as a famous specialist in ancient Lithuanian history, helped to acquire the books on history to the Lithuanian University. His remaining correspondence showed, that scientific works and books were bought from various countries from the East to the West. Parcels of books were sent from Poland and odered from H. Wilder, K. Fishler second-hand book-shops in Warshaw; from Gebethner, and Wolf bookstores in Krakow; also from the second-hand book-shops of Joseph Bayer in Frankfurt upon Main; Martin Breslauer’s in Berlin; Gustav Fock’s in Leipzig; Ludwig Häntzschel in Göltingen in Germany. The books were looked for in Paris (in France), in Prague (in Czechoslovakia) as well. Other books came from the RSFSR (Russia), the Ukraine (Kiev), Siberia (Tomsk). Many of them were received by the “Central Corporation of Mezhdunarodnaya Kniga” through it’s sections in Moscow and Leningrad. Some parcels of books were gained from individual persons and book-shops. This article points out what scientific works and historical books were bought for the Lithuanian university, indicates their prices, names significant themes and headings. Prof. I. Jonynas invited a pretty large number of people to participate in search for necessary books. Such famous scientists as academician S. Platonov, prof. I. Svencicki, S. Zaborowski, I. Savin, A. Andrejev and such experts of books as S. Meleščenka in Kiev helped him. Their letters, some of them unpublished, are cited in this article. Lithuanians living abroad helped in search of books too. The most distinguished among them was poet K. Sakalauskas-Vanagėlis (in Warszaw), diplomatists S. Lozoraitis (in Berlin), P. Klimas (in Paris) J. Brėdikis (in Prague) and others. Prof. I. Jonynas also applied to individual landlords and rare book collectors in Lithuania. All public and scientific activity of professor I. Jonynas and his like-minded persons, their cooperation with one another enriched the library of the Vytautas Magnus University and also induced the flourishing of science and culture in Lithuania.